The agencification of Europe: explaining the establishment of European Community agencies - Ekelund, Helena (2010)
Governance in the European Union is being transformed through the increased use of agencies to perform a range of functions in a variety of policy areas. The European Commission believes that agencies can add value but admits that their establishment has not been accompanied with a “common understanding” of their roles and purposes. In this thesis, I take the approach that such an understanding is best reached through examination of existing agencies. Focusing on the most common type of agency in the EU, i.e. Community Agencies, this thesis provides a four-level analysis. At the conceptual level, the thesis deals with the ‘agency’ concept. Drawing on public management literature, the empirical level involves classification of these diverse bodies. The contribution of the thesis at the theoretical level is to identify the key driving factors behind agency establishment; following a theoretical framework devised from new institutionalist theories I trace and analyse the establishment process of four case study agencies. The research reveals that to fully understand the establishment of agencies we need to draw on more than one strand of new institutionalism, as they can explain different aspects of agency creation. As a wider outlook the thesis reflects on the role of agencies, relating it to the wider academic debates on the ‘regulatory state’ and its implications for legitimacy.